2022
DOI: 10.1002/cam4.5152
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index and efficacy of pembrolizumab as second‐line therapy in patients with recurrent/metastatic head and neck squamous cell carcinoma

Abstract: Background Recent evidence suggested a potential correlation between BMI and the efficacy of immune checkpoint inhibitors in cancer patients. This study aimed to evaluate the prognostic value of the body mass index (BMI) in recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC) patients treat with pembrolizumab. Methods The current retrospective cohort study enrolled 49 R/M HNSCC patients underwent at least one cycle of pembrolizumab as second‐line treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In line with our results, a cross-cancer study by Johannet et al revealed that a BMI < 18.5 had no influence on PFS and OS [ 26 ]. In contrast, Zhang et al showed that low BMI was an independent marker for a worse clinical prognosis in R/M HNSCC patients receiving pembrolizumab [ 27 ]. These results suggest that the BMI may not be optimal for defining malnutrition in cancer patients receiving ICI [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with our results, a cross-cancer study by Johannet et al revealed that a BMI < 18.5 had no influence on PFS and OS [ 26 ]. In contrast, Zhang et al showed that low BMI was an independent marker for a worse clinical prognosis in R/M HNSCC patients receiving pembrolizumab [ 27 ]. These results suggest that the BMI may not be optimal for defining malnutrition in cancer patients receiving ICI [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, albumin decrease has been shown to be associated with rapid clearance of pembrolizumab in advanced cancer [ 31 ]. Second, the GNRI incorporates ideal weight into its calculation, which better resembles dynamic changes in chronic diseases such as tumor cachexia [ 26 , 27 , 32 ]. For example, Johannet et al showed that malnutrition, defined as weight loss six months prior to treatment, had a negative impact on immunotherapy response in non-small cell lung cancer, while baseline BMI did not [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been proved to be associated with the development of many chronic disease such as cardiovascular disease, type 2 diabetes, non‐alcoholic fatty liver disease, nephropathy and retinopathy 21–23 . In contrast, obese patients have also been reported to show better clinical prognosis in various cancers than their underweight counterparts 24–26 . This phenomenon is known as the obesity paradox.…”
Section: Discussionmentioning
confidence: 99%
“…In several cancer types, including non-small lung cancer (NSCLC), head and neck squamous cell carcinoma (HNSCC), and hepatocellular carcinoma (HCC), high BMI has been associated with better overall survival (OS). [20][21][22] Conversely, obese patients with renal cell carcinoma (RCC) have a significantly worse OS than normal weight patients. 23 With regard to the relationship between BMI and survival in metastatic urothelial carcinoma (mUC), limited studies have addressed this issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether BMI is a prognostic factor in the era of cancer treatment shifting toward immunotherapy remains unknown. In several cancer types, including non‐small lung cancer (NSCLC), head and neck squamous cell carcinoma (HNSCC), and hepatocellular carcinoma (HCC), high BMI has been associated with better overall survival (OS) 20–22 . Conversely, obese patients with renal cell carcinoma (RCC) have a significantly worse OS than normal weight patients 23 .…”
Section: Introductionmentioning
confidence: 99%